Exercise‐evoked intramuscular neutrophil‐endothelial interactions support muscle performance and GLUT4 translocation: a mouse gnawing model study. (13th December 2019) - Chaweewannakorn, Chayanit; Nyasha, Mazvita R.; Chen, Weijian; Sekiai, Shigenori; Tsuchiya, Masahiro; Hagiwara, Yoshihiro; Bouzakri, Karim; Sasaki, Keiichi; Kanzaki, Makoto
Abstract : Key points: Fractalkine receptor antagonist inhibited neutrophil recruitment to masseter muscles and exacerbated fatigability during masticatory activity. Fractalkine‐mediated neutrophil recruitment is required for both upregulation of myokines (CXCL1, interleukin‐6) and enhanced GLUT4 translocation in response to masticatory activity. Fractalkine and intercellular adhesion molecule‐1 expression in endothelial cells increased in response to masticatory activity. In vitro experiments demonstrated that contracting myotubes lack the ability to upregulate fractalkine but revealed that endothelial fractalkine upregulation is induced using a conditioned medium of contracting myotubes. Abstract: Physical exercise stimulates neutrophil recruitment within working skeletal muscle, although its underlying mechanisms remain ill‐defined. By employing a masticatory behaviour (gnawing) model, we demonstrate the importance of intramuscular paracrine and autocrine systems that are triggered by muscle contractile activity and reliant upon fractalkine/CX3CL1‐mediated signals. These signals were revealed to be required for achieving proper GLUT4 translocation and glucose uptake to meet the glucose demands for fatigue alleviation. Specifically, fractalkine expression and neutrophil recruitment both increased in the masseter muscle tissues upon masticatory activity. Importantly, a fractalkine antagonist inhibited neutrophil accumulation and exacerbated fatigability during masticatory activity. We found that fractalkine‐dependent neutrophil recruitment is required for both upregulation of myokines (i.e. CXCL1 and interleukin‐6) and enhanced GLUT4 translocation in response to gnawing activity. Immunofluorescence analysis of masseter muscles demonstrated that fractalkine and intercellular adhesion molecule‐1 expression are both upregulated in endothelial cells but not in myofibres. The in vitro exercise model further revealed that contractile activity failed to stimulate fractalkine upregulation in myotubes, implying that fractalkine is not a myokine (myofibre‐derived factor). Nevertheless, endothelial fractalkine expression was markedly stimulated by a conditioned medium from the contracting myotubes. Moreover, intercellular adhesion molecule‐1, a key adhesion molecule for neutrophils, was upregulated in endothelial cells by fractalkine. Taken together, our findings strongly suggest that endothelial fractalkine serves as a key factor for organizing a physiologically beneficial intramuscular microenvironment by recruiting neutrophils in response to relatively mild exercise (i.e. masticatory muscle activity). Key points: Fractalkine receptor antagonist inhibited neutrophil recruitment to masseter muscles and exacerbated fatigability during masticatory activity. Fractalkine‐mediated neutrophil recruitment is required for both upregulation of myokines (CXCL1, interleukin‐6) and enhanced GLUT4 translocation in response to masticatory activity. Fractalkine and intercellular adhesion molecule‐1 expression in endothelial cells increased in response to masticatory activity. In vitro experiments demonstrated that contracting myotubes lack the ability to upregulate fractalkine but revealed that endothelial fractalkine upregulation is induced using a conditioned medium of contracting myotubes.